2013
DOI: 10.1016/j.riai.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Los Sistemas de Suspensión Activa y Semiactiva: Una Revisión

Abstract: El propósito de este artículo es efectuar una revisión del estado del conocimiento en el modelado y control de los sistemas de suspensión activa y semiactiva. Se analizan las principales características de los diferentes tipos de sistemas de suspensión: pasiva, activa y semiactiva. Respecto al modelado y simulación de los sistemas de suspensión, se examinan los distintos enfoques, herramientas y aplicaciones en el contexto de la dinámica vehicular. Además, para el modelo de un cuarto de vehículo, ampliamente u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 131 publications
0
2
0
1
Order By: Relevance
“…Los edificios sin estos dispositivos sobreviven el sismo severo disipando energía en sus elementos principales, los que finalmente sufren el mayor daño. Si la estructura es sometida a deformaciones que puedan llegar a ser excesivas, esto se podría reflejar en un desempeño estructural deficiente, que podría conducir a situaciones altamente indeseables, tal como los elevados costos de rehabilitación por los daños en los elementos no estructurales [31].…”
Section: Introductionunclassified
“…Los edificios sin estos dispositivos sobreviven el sismo severo disipando energía en sus elementos principales, los que finalmente sufren el mayor daño. Si la estructura es sometida a deformaciones que puedan llegar a ser excesivas, esto se podría reflejar en un desempeño estructural deficiente, que podría conducir a situaciones altamente indeseables, tal como los elevados costos de rehabilitación por los daños en los elementos no estructurales [31].…”
Section: Introductionunclassified
“…For example, magnetorheological dampers [ 27 ], which incorporate magnetic particles suspended in a viscous liquid, can alter their rheological properties by the application of an external magnetic field [ 28 , 29 ]. In other cases, the application of external energy to a motor acting on the suspension allows the appropriate damping characteristic to be achieved [ 30 ]. Recently, studies on energy recovery dampers have shown that it is possible to change the comfort characteristics by varying the electrical parameters of the generator [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Karnopp’s study (1989), a linear permanent magnet machine that can be used as a variable damper was presented, but it did not go deep into the semi-active suspension system operation. Some other references explain aspects of semi-active damping systems without specifying the type of shock absorber, for instance, Ezeta et al (2013) and Jalili (2002) discussed semi-active suspension systems but did not mention electromagnetic dampers. Paulides et al (2006) used analytical and numerical resources to recommend a design of tubular linear damper for semi-active suspension systems.…”
Section: Introductionmentioning
confidence: 99%